The Conclusive Phase of Civil Case Resolution: Examining Execution and Post-Decision Challenges in Indonesian Civil Procedural Law - Retno Kus Setyowati (Universitas Negeri Semarang, 2023)
The culmination of a civil case in court is marked by the crucial step of decision implementation, commonly known as execution. Execution can only proceed when the decision attains permanent legal force ('inkracht van gewijsde'). While the losing party may voluntarily execute the decision, failure to fulfill stipulated obligations empowers the winning party, the plaintiff, to seek forced execution. Despite the irrevocable legal status of a decision, as signified by its permanent legal force, Indonesian civil procedural law affords opportunities for litigants and third parties to reassess such decisions. This reassessment is facilitated through challenges or rebuttals, as outlined in Article 195 paragraph (6) HIR, Article 206 paragraph (6) Rbg, Article 378 RV, Article 279 RV, and is guided by the Ius Curia Novit principle, as affirmed in Article 10 of Law Number 48 of 2009 concerning Power Justice. Utilizing a normative juridical approach, this study relies on secondary data to explore the nuances of execution and post-decision challenges, drawing on primary legal materials, secondary legal materials, and tertiary legal materials.